Investigating the Effects of Two Functional and Extra-Functional Stretching Methods of the Leg Muscles on a Selection of Kinematic and Kinetic Indicators in Women with Ankle Instability - Samaneh Karajiban Maher; Abdolrasoul Daneshjoo; Behzad Divkan (Islamic Azad University, Hamedan Branch, 2023)
Objective The purpose of the present study was to investigate the effects of two functional and functional stretching methods of the leg muscles on a selection of kinematic and kinetic indicators in women with ankle instability. Methods 24 people were selected and randomly divided into the functional exercise (8 persons), extra-functional exercise (8 persons) and control (8 persons) on the basis of inclusion and exclusion criteria. The experimental group underwent stretching exercises for eight weeks, 3 sessions each week, and the control group was merely performing its daily activities. Then, in order to measure the pre -test and post -test variables, the dorsiflexion, Plantar flexion and ground reaction force were investigated and measured. Data was analyzed using paired-samples T test and independent-samples T -tests at a significant level of 0.05 All statistical reviews were conducted using SPSS software version 25. Results The results of the T -test showed the significant effect of eight weeks of functional and Extra functional exercises on dorsiflexion, Plantar Flexion and ground reaction force. (P≤ 0/001). Conclusion The results of this study showed that the implementation of the functional and Extra-functional exercise protocol has an impact on the amount of Ankle dorsiflexion and the Plantar flexion of the Girls with an ankle instability. It was also found that muscle flexibility following the stretch ability of the gastrocnemius muscles by affecting the amount of wrist flexion facilitates the walking of the wrist installation, so these people are recommended to use the functional and Extra-functional exercise protocol.